Performance improvement in a heat exchanger tube using discrete XV baffle (DXVB) turbulators - Amnart Boonloi; Nuttawut Lewpiriyawong; Withada Jedsadaratanachai (My University, 2024)
Thermal performance improvement in a heating tube (HT) using discrete X–V baffle (DXVB) as turbulators is presented. The DXVB is designed with two main goals: 1. To decrease the pressure drop in the tested tube and 2. To increase the mixing quality in the heat exchanger tube and 3. To produce powerful vortex flows. Lower pressure drop, generated vortex flows and higher mixing quality will augment a heat transfer rate and thermo-hydraulic efficiency. This study examines effects of DXVB structures, DXVB distances and placements on laminar air flow and thermal structure with Reynolds number from 100 to 2000. The current problem is numerically investigated using the finite volume technique of a commercial program/code (ANSYS-FLUENT V.2022). The created model of the HT fitted with the DXVB is numerically validated. From the numerical results, the DXVB installed affects the air flow structure in the tested tube. The vortex streams are observed. The change in fluid flow influences thermal characteristics. The vortex streams destroy some parts of the thermal boundary layer and help to increase mixing quality. These perturbed thermal boundary layer (TB-layer) and better mixing quality are two important factors that contribute to convective heat transfer enhancement. In addition, the maximum heat transfer rate and pressure loss are 10.17 and 45.75 times upper than that in the circular plain tube, respectively, while the best thermal enhancement factor (TEF) of 3.09 is observed at 15b5g, +x at Re = 2000.
Keywords: Turbulator; Baffle; Heat transfer enhancement; Heat Transfer Mechanisms